Transnasal Endoscopic Surgical Repair of Cerebrospinal Fluid(CSF) Rhinorrhea by Inferior Turbinate Grafts - Muhammad Saleem, Naeem ur Rehman, Raina Khan, Ashar Alamgir, Sarwat Bibi, Humaira Ahmad (Journal of Rawalpindi Medical College, 2021)
Objective: The study aims to evaluate the outcomes of transnasal endoscopic surgical repair of CSF rhinorrhoea. Materials and Methods: After approval from the institutional ethical committee (DME-396-18) and patient consent, a descriptive study of 27 patients with cerebrospinal fluid rhinorrhea was conducted at Aziz Fatimah Trust Hospital Faisalabad from August 21, 2018, to February 7, 2021. Transnasal endoscopic surgical repair of Cerebrospinal fluid leak was performed by using multilayer technique using a graft from the inferior turbinate. The data collected were analyzed using SPSS 20. Results: The most common site of the CSF leak was the left side of the cribriform plate (n=19,70%). The most common etiology was spontaneous (n=16,59%). At the same time, traumatic CSF leak (n=16,59%). was the second common etiological factor. The surgical procedure used in the study reported a 93%(n=25) success rate. The success rate was 97.5% on revision surgeries. Conclusion: Transnasal endoscopic surgical repair of CSF leak is one of the most effective and safe surgical interventions. Multilayer technique is not only safe but also has lesser complications. Moreover, this minimizes the risk for the development of secondary wounds as compared to other surgical processes.